PENGARUH ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) TERHADAP EARNINGS MANAGEMENT YANG DIMODERASI OLEH BOARD GENDER DIVERSITY PADA ASEAN-5 - Wijaya Triwacananingrum; Nasyrul Adha Akhnafulloh (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
The purpose of this study is to empirically examine the impact of Environmental, Social, and Governance (ESG) performance practices on earnings management, using gender diversity as a moderating variable. This research focuses on non-banking companies in five ASEAN countries: Indonesia, Malaysia, the Philippines, Singapore, and Thailand, from 2015 to 2024. The sampling was purposive, based on a total of 1,310 observations analyzed using panel data regression and the Fixed Effects Model. Labor management variables were evaluated using Kothari's (2005) Absolute Discretionary Accruals model, while ESG work practices were evaluated using Refinitiv scores. Research findings indicate that ESG has a significant and negative impact on labor management. This illustrates Agency Theory, which states that ESG commitment effectively enhances transparency and drives managerial opportunities. However, the moderation results indicate that gender differences do not significantly affect the relationship between ESG and workforce management. This indicates that female directors in ASEAN have not yet reached a critical mass, with an average of 14.49 percent, making their impact more symbolic than substantial in terms of oversight. The implication of this research is that investors are advised to use the ESG score as a reliable primary indicator in assessing risk and the quality of financial reports, regardless of the current gender composition of the board.